Addressing new challenges for a community music project in the context of higher music education: A conceptual framework (UCL Press, 2017)
In response to Europe's societal challenges, such as current issues about migration, the Institute of Music Education at the University of Music and Performing Arts Graz established Meet4Music (M4M), a low-threshold community music project. M4M is open to individuals from all sociocultural and musical backgrounds and ages, and provides them with the opportunity to socialize with others and to express themselves musically. M4M is based on collaborative learning in an open community ensemble, which includes choir, dance, theatre and percussion, alternating with one another on a weekly basis. University students can choose M4M as an elective course to gain relevant experience in leading heterogeneous and intercultural ensembles. The aim of this paper is to present this project, with a special focus on its dimensions, aims and pedagogical implications for educating reflective teachers. A conceptual framework that contributes to the concept of lifelong learning in (higher) music education will be provided, and foundations for further research and theory will be offered.